2006
DOI: 10.1007/s00508-006-0582-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid hemangioendothelioma derived from the spine region: Case report and review of the literature

Abstract: Epithelioid hemangioendotheliomas (EHE) are rare vascular tumors which generally originate from soft tissues and visceral organs. Primary bone EHEs, especially those occurring in the spine region, are extremely rare. Our case is that of a 30-year-old man who was admitted to hospital with low back pain, difficulty in walking, post-voiding urinary incontinence and numbness in the caudal area. X-ray showed a lytic process affecting the vertebra L2 and collapse of L1. Vertebrectomy of L1 and gross total tumor rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In 2008, Deyrup et al11 reported 49 cases of EH of soft tissues in total, and the majority of cases are associated with low mortality, but some metastasize and cause patient death. Many other sites of involvement of bones and soft tissues are possible, such as the maxilla, spine region, the head and neck region, but to our knowledge, only few cases have been reported12-17. When there is lower extremity involvement, multicentric epithelioid hemangioendothelioma has been known to involve the femur, tibia, phalange, cuneiform, tarsal navicular and metatarsal bone either as the first or subsequent tumor but multiple involvement of bones and soft tissue in the same lower extremity is very rare (Table 1) 5, 18-23.…”
Section: Discussionmentioning
confidence: 96%
“…In 2008, Deyrup et al11 reported 49 cases of EH of soft tissues in total, and the majority of cases are associated with low mortality, but some metastasize and cause patient death. Many other sites of involvement of bones and soft tissues are possible, such as the maxilla, spine region, the head and neck region, but to our knowledge, only few cases have been reported12-17. When there is lower extremity involvement, multicentric epithelioid hemangioendothelioma has been known to involve the femur, tibia, phalange, cuneiform, tarsal navicular and metatarsal bone either as the first or subsequent tumor but multiple involvement of bones and soft tissue in the same lower extremity is very rare (Table 1) 5, 18-23.…”
Section: Discussionmentioning
confidence: 96%
“…Luzzati et al (14) reported pathological fracture in eight out of ten cases in their series. Soft-tissue extensions can lead to neurologic compression, which result in neurologic symptoms such as paresthesia, weakness, and paraplegia (1,5,7,8,15,29,(32)(33)(34)36,(41)(42)(43)(44)(45).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The tumor cells show endothelial differentiation characterized by intracytoplasmic inclusions seen as vacuoles and containing erythrocytes. 26 The prognosis of the tumor depends on its histopathological features and location. 27 Angiosarcomas are derived malignant endothelial cells lining anastomotic vascular channels.…”
Section: Vascular Tumorsmentioning
confidence: 99%